The Impact Profitability, Leverage and Firm Size on Disclousure of Corporate Social Responsibility - Sulastri; Arivetullatif; Ilham Multama (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of profitability, leverage and company size on the disclosure of corporate social responsibility. The independent variables in this study are profitability, leverage and firm size, while the dependent variable is corporate social responsibility. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018 2021. The data used in this study are annual report data and a quantitative approach. The sampling method used purposive sampling method. The analytical method used in this study used multiple linear regression analysis with the help of SPSS (Statistical Product and Services Solutions) version 25. The number of samples in this study were 36 observations in 9 companies observed for 4 years. The results of this study indicate that profitability, leverage and company size have no effect on corporate social responsibility. Taken together, the same profitability, leverage and company size do not affect the disclosure of corporate social responsibility.